INFORMATION OBJECTS IN THE GLOBAL COMMUNICATION NETWORK (Modern education and development, 2025)
The rapid expansion of global communication networks has led to the proliferation of information objects, which play a crucial role in data exchange, knowledge dissemination, and digital interactions. This paper examines the nature, classification, and significance of information objects within the global communication infrastructure. It also explores the challenges associated with data security, integrity, and accessibility, as well as emerging trends in artificial intelligence and blockchain technologies for optimizing information management.